The Impact of Socioeconomic Status on Satisfaction with Nursing Care Quality among Post Operative Patients in xuzhou, China - Zhang, Ziyang; Maxima M. Floranda, Lualhati (Journal of Neonatal Surgery, 2025)
summary Objective: To explore the role of socioeconomic status in patient satisfaction with quality of nursing care among postoperative patients in the Xuzhou area of China. Method: Between September and December 2024, a cross-sectional survey was carried out using a self-reporting questionnaire in three tertiary hospitals in Xuzhou, which is one of the fastest-urbanizing districts in Jiangsu Province. The simplified Chinese version of the Cancer Nursing Quality Scale was used, and 462 valid questionnaires were analyzed with SPSS26.0. Results: The average nursing satisfaction score was 143.79±15.296. Univariate and multivariate analysis revealed that level of education, working hours, and occupation significantly affected satisfaction. Patients with a higher level of education and cadre occupations were less satisfied, while those who worked longer hours were more satisfied. But patients who had a master's degree or higher did not follow the same pattern. Conclusion: Socioeconomic characteristics, especially work-related and educational qualities, play crucial roles in shaping perceived quality of nursing care. Interventions tailored to fit the individual requirements of different groups of patients ought to be prepared.